2012
DOI: 10.4995/wrs.2012.1232
|View full text |Cite
|
Sign up to set email alerts
|

Activity of diclazuril against coccidiosis in growing rabbits: experimental and field experiences

Abstract: AbstrAct:The efficacy of diclazuril in growing rabbits was investigated under experimental and field conditions. In a first experimental trial, the susceptibility of recent isolated French Eimeria field strains to in-feed use of diclazuril, salinomycin and robenidine was studied in fattening rabbits. Rabbits were challenged at the age of 31 d with a mixed inoculum of Eimeria magna, E. media and E. perforans. Production data and oocyst excretion were compared with an infected-untreated control group and an unin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 3 publications
3
10
2
Order By: Relevance
“…Efficacy of subcutaneously administred diclazuril against Eimeria infection was demonstrated by Pan et al [34]. Furthermore, the superior efficacy of diclazuril in elimination of oocysts shed has been reported in several rabbit studies [13, 18, 21, 35]. Effectiveness of sulphachloropyrazine when used curatively against clinical coccidiosis reported in the present study agrees with an earlier study by Kolabskii et al [36].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Efficacy of subcutaneously administred diclazuril against Eimeria infection was demonstrated by Pan et al [34]. Furthermore, the superior efficacy of diclazuril in elimination of oocysts shed has been reported in several rabbit studies [13, 18, 21, 35]. Effectiveness of sulphachloropyrazine when used curatively against clinical coccidiosis reported in the present study agrees with an earlier study by Kolabskii et al [36].…”
Section: Discussionsupporting
confidence: 91%
“…Our study demonstrated the superior efficacy of curative use of diclazuril and sulphachloropyrazine against rabbit coccidiosis. Similar efficacies following curative use of diclazuril in resolving clinical signs of coccidiosis have been reported in other studies [18, 21] even against Eimeria spp. resistant to other anticoccidial drugs [20].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Among Eimeria species responsible for natural coccidial infections in animals examined in this study, E. perforans and E. magna are included among the most frequent species reported in farm rabbits in Italy (Gallazzi, 1977;Vereecken et al, 2012), while the prevalence of E. exigua is lower (Vereecken et al, 2012). As for their pathogenicity, E. perforans and E. exigua are considered slightly pathogenic, while E. magna is considered mildly pathogenic to pathogenic Bhat et al 1996;Pakandl 2009).…”
Section: Discussionmentioning
confidence: 99%